Letter (copy) : Hogar Espanol
001-0107-001 International AEC/MC/1402 17th August 1944 Mr Norman Todd, Ilford Trades Council and Labour Party 35 Penrith Road Hainault Ilford, Essex Dear Mr Todd, Hogar Espanol I have your letter of the 15th August in which you inform us that you have received an appeal for funds from the above body. For your information we may say that the organisation in question is a communist body and that the General Council have no relations with it whatsoever. In this connection I recall the interest you showed in the scheme which we submitted to Trades Councils for assistance in trade union reconstruction in Europe. Quite apart from the issue of communism in this particular connection your Council can do most work by concentrating all its efforts in the realm of international solidarity in securing from your area the maximum possible response to the appeal which we have sent out. Yours sincerely, Secretary International Department 292/946/1/107